The Experiential Exercise Situation: A Comment on Instructional Role and Pedagogy Evaluation - Certo, Samuel C. (Academy of Management Review, 1976)
In this article the author examines the effectiveness of using experiential exercise learning materials in management education. He notes that in this method students actively participate in the performance of a goal-oriented task and learn both from the task itself as well as from a subsequent evaluation of the performance. He adds that the effectiveness of this method is largely attributed to the effectiveness of the instructor. He outlines a generally used role of the instructor of these methods discussing how to maximize the experiential learning effects as well as the importance of this role in the evaluation of the method.